Google Sites en el aprendizaje de Lengua y Literatura del 7mo “B”, escuela de Educación Básica “Miguel Riofrío”. Período 2021 - 2022. - Malan Ramírez, Lizbeth Paola (2022)
The use of Google Sites has involved the active participation of ICTs as a source of support in the reinforcement of basic content that students must achieve for their training in the subject of Language and Literature. In view of this, we proceeded to raise the first specific objective where we diagnosed the learning level of the students in which it was delimited that within the subject investigated five curricular blocks are involved, which is why we took as instruments to evaluate the PROLEC-R evaluation battery to diagnose the reading level and the PROESC evaluation battery for the diagnosis of the writing processes. On the other hand, the second objective consisted of executing an alternative proposal in which the difficulties presented by the students were taken into account, as well as the contents addressed in the unit of study, designing sessions that allowed reinforcing their knowledge. Consequently, in objective three, the impact of the tool was evaluated within the students' learning and thanks to the application of the evaluation batteries, a pre- and post-test was applied where significant results were obtained, thus achieving the general objective by determining the importance of Sites in learning. It is also important to point out that this research was sustained in a mixed approach (quali-quantitative) that also maintained a quasi-experimental and descriptive design and therefore the technique used was the survey (applied to the teacher) and the written test (applied to the students) and as an instrument the questionnaire, thus establishing the validity of this research work which is relevant in the academic field, whose results generated that the students' learning is interactive and motivating creating dynamic environments. Keywords:, ICT in Education, Language and Literature, Google Sites, Teaching Resources, Learning Strategies.